2019
DOI: 10.1002/ejsp.2638
|View full text |Cite
|
Sign up to set email alerts
|

Too great to act in solidarity: The negative relationship between collective narcissism and solidarity‐based collective action

Abstract: Three studies examined the association between narcissistic identification with one’s advantaged in‐group and engagement in solidarity‐based collective action. Drawing on theory and past research, a negative effect of collective narcissism on solidarity‐based collective action was expected. A two‐wave longitudinal study (N = 162) found that Polish participants’ narcissistic, but not secure, national identification decreased their willingness to engage in collective action in solidarity with refugees over time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 93 publications
(151 reference statements)
6
62
0
1
Order By: Relevance
“…The present results extend and complement previous findings indicating that male collective narcissism is negatively related to men's solidarity with women's collective actions against gender discrimination (Górska et al 2019). The present results elucidate that male collective narcissism is associated with sexism and endorsement of gender inequality when men feel their masculinity is threatened.…”
Section: Male Collective Narcissism and Sexismsupporting
confidence: 88%
See 2 more Smart Citations
“…The present results extend and complement previous findings indicating that male collective narcissism is negatively related to men's solidarity with women's collective actions against gender discrimination (Górska et al 2019). The present results elucidate that male collective narcissism is associated with sexism and endorsement of gender inequality when men feel their masculinity is threatened.…”
Section: Male Collective Narcissism and Sexismsupporting
confidence: 88%
“…In line with previous research indicating that collective narcissism is related to prejudice toward out-groups perceived as threatening Golec de Zavala et al 2009;Lyons et al 2010), studies showed that male collective narcissism (but not nonnarcissistic positive gender identification) was associated with perceived threat from women (Górska et al 2019). Previous research has also shown that collective narcissism is associated with intergroup hostility because of the perception of the in-group as threatened (Golec de Zavala et al 2009;Golec de Zavala and Cichocka 2012).…”
Section: Intergroup Perspective: Male Collective Narcissism and Sexismsupporting
confidence: 87%
See 1 more Smart Citation
“…Because of the lack of trust towards other groups, collective narcissism also predicts generalized prejudice towards members of groups that tend to be perceived as threatening by ingroup members. For instance, American collective narcissism predicted prejudicial attitudes towards Chinese (Cai & Gries, ), Arabs (Lyons, Kenworthy & Popan, ) and undocumented Latinos (Lyons, Coursey, & Kenworthy, ), while Polish collective narcissism predicts lower concern for refugees (e.g., Górska et al , ), anti‐Semitism (Golec de Zavala & Cichocka, ), and prejudice towards ethnic minorities more broadly (Cichocka, Dhont, & Makwana, ; Golec de Zavala, Cichocka, & Bilewicz, ; for evidence from longitudinal research see Cichocka, Golec de Zavala et al , ). These effects of collective narcissism are usually observed when controlling for ingroup identification.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies mostly focused on collective narcissism in the national context (e.g., , only occasionally applying it to other groups, including gender (Górska et al, 2020) and business (Cichocka, 2016), religious (Marchlewska, Cichocka, Łozowski, Górska, & Winiewski, 2019) or extremist (Jasko et al, 2020) organisations. Here, we examine the role of collective narcissism within the political party context.…”
Section: Discussionmentioning
confidence: 99%